Analysis of Alternative Dispute Resolution in non-litigation dispute resolution on Islamic Mortgage: at the Ombudsman Institution Yogyakarta - Mulyono Jamal; Akhmad Afandi Mahfudz; Syamsuri Syamsuri; Resi Handayani (Universitas Darussalam Gontor, 2021)
Limited information, experience, and very low economic conditions are the background of business dispute cases, especially in Islamic mortgages. Business dispute cases, including Islamic mortgage, have so far been resolved using non-litigation settlements using Alternative Dispute Resolution (ADR), it is considered easier, does not incur expensive costs, is familial, and achieves the goal of dispute resolution, namely win-win solutions. Settlement of disputes using this method has been regulated in Law Number 30 of 1999 concerning arbitration and alternative dispute resolution. In this case, the Yogyakarta Ombudsman as one of the non-litigation institutions also takes part in resolving disputes non-litigation. This study aims to analyze the method used, namely alternative dispute resolution in resolving disputes over sharia mortgage loans. Finally, this research finds that in the process of resolving disputes over sharia mortgages with alternative dispute resolution, the method of consultation, negotiation, mediation, and expert judgment is used. The alternative dispute resolution method prioritizes peace and a win-win solution or conditions that are favorable to the parties, but in this case, the non-litigation dispute resolution method does not succeed in bringing about peace or a win-win solution.